Assessment of vulnerability to fluvial floods: Case of municipalities of the Gidra River Basin, Slovakia - Matej Vojtek; Soheyl Moradi (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The aim of this study is to assess the vulnerability of municipalities located in the Gidra River Basin to fluvial floods. We have calculated a fluvial flood vulnerability index (FFVI) related to the year 2021 for twelve municipalities, which fall into the Gidra River Basin and whose urban area is completely or partially located in the basin, and at the same time a watercourse, belonging to the Gidra River Basin, flows through the municipality.